EP.TH.717Triple tumour: A myriad of serial incidental findings in a patient presenting with Gallstone pancreatitis. (28th October 2021) - Boyle, Cameron; Lowe, Katherine; Dhaif, Ahmed; Hassan, Adeeb; Shalli, Kawan; Gumber, Ashutosh
Abstract: Aim: To present a rare incidental synchronous triple tumours - colonic adenocarcinoma, endometroid ovarian adenocarcinoma and benign Brenner tumour in a patient admitted with acute gallstone pancreatitis. Methods: A 75-year-old female presented with epigastric pain. Blood-tests and USS abdomen confirmed gallstones and pancreatitis. She was treated conservatively. USS also showed incidental pelvic mass which was further characterised by CT and MR scans. These scans confirmed heterogeneous lobulated mass in the left adnexa. CT scan also picked-up incidental mass in transverse colon, which was confirmed as cancer by colonoscopy. She was offered therapeutic resection after discussion in Colorectal and Gynaecology MDT. Intra-operatively, transverse colonic tumour was invading into the proximal ileum. Laprascopic surgery concluded with extended right hemicolectomy, small bowel resection-anastomosis, omentectomy, total abdominal hysterectomy and bilateral salpingo-oophorectomy. Results: The patient had gradual recovery without any complications. Histopathology showed T4N2 poorly differentiated adenocarcinoma of colonic mass, FIGO grade 1 stage 1c endometrioid adenocarcinoma of left ovary and benign brenner tumour of right ovary. Post-operative MDT did not offer adjuvant-therapy due to slow recovery and fraility. So far, two-years of follow-up did not show any recurrence. Conclusion: This report adds to the limited literature of triple synchronous tumours, including rare Brenner accounting for 5% of benign ovarian tumours and endometrioid ovarian tumour with an incidence of 4 -7%. Multi-disciplinary approach and combined surgery can achieve a desirable outcome in such complex cases. It is crucial to identify the primary status of the tumours as it will guide the adjuvant treatment.